Lifestyle and Chronic Constipation in Medical Students - Mehmet Aykut Yildirim; Murat Cakir; Mehmet Bicer; Mustafa Senturk; Harun Yonar; Merve Nur Gur; Zeliha Nur Akiner; Ayse Guldiken; H. Kaan Karagul; Bugra Ceri (Gastroenterology Research and Practice)
Aim. Constipation is one of the most common complaints of the digestive system indicated with an increase in defecation frequency, difficulty in defecation, and hard and strained defecation. Environmental, personal, and genetic factors may be affecting constipation although the affecting factors have not yet been thoroughly explained. The aim of this study was to investigate constipation frequency and lifestyles in medical students. Method. The population was selected among medical students for the study, which was planned as a survey study. Demographic data of all the participants and the factors suggested to affect constipation were questioned and analyzed. Results. The study covered a total of 425 medical students. Among the students reporting constipation, 2.86% were in their first year of medical school, while 7.53% were in the third year and 9.09% were in the sixth year. The rate of students reporting constipation and familial history was statistically significant. While regular eating habits were reported in the first and third years, this rate was much lower in the sixth year group working at clinical departments. The results of our study did not reveal any significant relationship between daily intake of water and constipation. There was, however, a significant relationship between stress and constipation. Conclusion. The results of our study showed that medical education did not curb constipation frequency. We believe that stress is significant in constipation. The data we collected indicate that regular eating habits and excess liquid intake are not as effective as suggested in the treatment of constipation.